Peran Media Digital dalam Meningkatkan Partisipasi Politik: Studi pada Tirto.id di Yogyakarta - Zubaidi, Ahmad; Jauhary, Moh. Wildan; Lestari, Lia (Sekolah Pascasarjana UGM, 2020)
Digital mass media is expected to provide educational information about politics in order to raise the political participation of its readers. This article aims to explain the role of digital media in increasing political participation, the obstacles it faces, and its solutions, by looking at Tirto.id.This research was a descriptive qualitative research. Research data was collected through in-depth interviews and participatory observation and focus group discussion. They were complemented with literature study and online research to obtain secondary data. The result of this research was that as a digital media, Tirto.id exists with its vision and mission as press media in providing actual reports while maintaining credibility. To this day Tirto.id maintains the values and rules mandated in the press law to continue providing information, education, entertainment and social control . Tirto.id plays its role in increasing political participation, as seen in its readersâ€™ many responses to its reports, especially with regard to political news which was connected to its social media.Â It is also evidenced in how Tirto.id keeps its credibility by giving data-based balanced information data, validated through data checking and independent research, as well as its writer columns, though the latter is still limited.